European private international law and member state treaties with third states : the case of the European Succession Regulation / edited by Anatol Dutta, Wolfgang Wurmnest. - Dutta, Anatol; Wurmnest, Wolfgang (Intersentia, 2019)
Several Member States of the European Union have concluded treaties and conventions with Third States dealing with questions of succession law in cross-border matters. Some of these treaties originate from the beginning of the 20th century and are outdated. The European legislator, however, cannot supersede these treaties and conventions unilaterally with its regulations, in fact they enjoy priority over the European Succession Regulation. The harmonizing effect of European private international law is hence endangered, the more so, as these treaties and conventions often cover large groups of third State nationals in the respective Member State. This book analyzes the background, scope and practical impact of bilateral treaties and multilateral conventions concluded by selected Member States of the European Union with third States, both from the European and the third State perspective. It evaluates the impact of these treaties and conventions on the functioning of the European Succession Regulation and the possibilities to facilitate the interplay between these instruments and European private international law. Anatol Dutta holds a Chair of Private Law, Private International Law and Comparative Law at the Ludwig Maximilians University Munich. Wolfgang Wurmnest holds the Chair of Private Law, Commercial Law, Private International and Comparative Law at the University of Augsburg.